Changes in the antigenic and genetic structure of influenza viruses: analysis of surveillance data of influenza A and B in Russia in 2006-2013 (Microbiology Independent Research Journal, 2015)
The goal of this research project was to study the natural variability of human influenza A and B viruses based on the analysis of the population structure of influenza viruses, circulating in Russia in 2006-2013, in order to determine the direction of their genetic and antigenic drift by comparison to the WHO reference strains. Our results proved that during that period significant changes occurred in the genetic structure of influenza viruses, their phylogenetic affiliation, as well as their sensitivity to antiviral drugs. According to the surveillance data, the percentage of influenza A(H1N1) viruses among patients with influenza-like illness or acute respiratory infection gradually decreased from 42% of the total number of influenza viruses in 2006-2007 to 19% in 2008- 2009. Influenza A(H1N1) viruses are characterized by «silent» variability that manifests in the gradual accumulation of amino acid substitutions in the minor undetectable group of viruses.The share of influenza A(H3N2) viruses varied from 10% in the 1st post pandemic year to approx. 60% in 2008-2009 and 2011- 2012 epidemic seasons. All of the influenza A strains isolated during the last years of the period, covered in this study, were found to be susceptible to neuraminidase inhibitors and resistant to adamantane antivirals.Influenza B viruses of both Yamagata and Victoria lineages circulated in Russia in the period from 2006 to 2013. The vast majority of these influenza B viruses belonged to the Victoria lineage. Phylogenetic and antigenic analyses of influenza B viruses have demonstrated a gradual drift of Russian isolates from the reference strains. No changes leading to resistance to oseltamivir or zanamivir were found in influenza B strains isolated until 2013.